Genome-wide identification and characterization of Puccinia striiformis-responsive lncRNAs in Triticum aestivum - Das, Parinita; Grover, Monendra; Mishra, Dwijesh Chandra; Guha Majumdar, Sayanti; Shree, Bharti; Kumar, Sundeep; Mir, Zahoor Ahmad; Chaturvedi, Krishna Kumar; Bhardwaj, Subhash Chander; Singh, Amit Kumar; Rai, Anil (Frontiers in Plant Science, 2023)
Wheat stripe rust (yellow rust) caused by Puccinia striiformis f. sp. tritici (Pst) is a serious biotic stress factor limiting wheat production worldwide. Emerging evidence demonstrates that long non-coding RNAs (lncRNAs) participate in various developmental processes in plants via post-transcription regulation. In this study, RNAseq was performed on a pair of near-isogenic line: rust resistance line FLW29 and rust susceptible line PBW343 that differed only in the rust susceptibility trait. We identified a total of 6807 lncRNA transcripts using bioinformatics analyses, among which 10 lncRNAs were found to be differentially expressed between resistance and susceptible line. In order to find the target genes of the identified lncRNAs, their interactions with wheat microRNA (miRNAs) were predicted. A total of 199 lncRNAs showed interactions with 65 miRNAs, which further targets 757 distinct mRNA transcripts. Moreover, detailed functional annotations of the target genes were used to identify the candidate genes, pathways, domains, families and transcription factors that may be related to stripe rust resistance response in wheat plants. The NAC domain protein, disease resistance protein RPP13 and RPM1, At1g58400, monodehydroasorbate reductase, NBS-LRR-like protein, rust resistance kinase Lr10-like, LRR receptor, serine/threonine-protein kinase, and cysteine proteinase are among the identified targets that are crucial for wheat stripe rust resistance. Semiquantitative-PCR analysis of some of the differentially expressed lncRNAs reveled variation in expression profiles of two lncRNAs between the Pst resistant and susceptible genotypes at least under one condition. Additionally, SSRs were also identified from wheat lncRNA sequences which may be very useful for conducting targeted gene mapping studies of stripe rust resistance in wheat. Thes findings improved our understanding of molecular mechanism responsible to the stripe rust disease that can be further utilized to develop wheat varieties with durable resistance to this disease.